Collected works of the Fourth Mtshan-ñid Sprul-sku of Rdza-stod ʼJam-dpal-nor-bu - ʼJam-dpal-nor-bu, Rdza-stod Mtshan-ñid Sprul-sku IV, 1892-1960 (Sonam Topga, 1974)
Writings, chiefly on Nyingmapa and Drukpa Kargyudpa Lamaisr ritual, of a scholar from eastern Tibet.